Implementation of Cross Border Insolvency Regulations in Bankcruptcy Cases in Indonesia - Halida Rahardhini; Joni Emirzon; Hasim Purba; Dedi Harianto (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
Complex bankruptcy issues are still possible, notwithstanding the rise in trade between businesspeople of different nationalities, particularly in cases of cross-border insolvency or bankruptcy that transcend national borders. The severity of the issues in cross-border insolvency proceedings in Indonesia is increased by the lack of consistency or harmonization of bankruptcy laws (statutory regulations) throughout nations worldwide about proposed bankruptcy rulings. This study employs the Normative Juridical research method, emphasizing literature reviews using relevant Indonesian laws and regulations and several relevant book references. It also takes an analytical descriptive approach. The following research findings were derived from the studies that were conducted: Efforts to create legal products that agree on cross-border bankruptcy laws in order to tackle global economic integration, particularly in the ASEAN region, are greatly aided by the UNCITRAL Model Law on Cross-Border Insolvency with Guide to Enactment. Indonesia may choose to implement the Model Law in light of ASEAN's economic cooperation. Only three articles—Articles 212, 213, and 214—of the Bankruptcy Rules now in force govern international matters. These three paragraphs do not govern the technique and process of execution; they solely deal with the transfer of assets included in bankruptcy overseas and the transfer of all or a portion of debts or receivables to third parties.